2016
DOI: 10.1186/s12872-016-0403-3
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and mortality in patients undergoing coronary artery bypass graft (CABG)-a register-based cohort study

Abstract: BackgroundPrevious studies have shown that compared with abstinence and heavy drinking, moderate alcohol consumption is associated with a reduced risk of mortality among the general population and patients with heart failure and myocardial infarction. We examined the association between alcohol consumption and mortality in coronary artery bypass graft (CABG) patients.MethodWe studied 1,919 first-time CABG patients using data on alcohol consumption and mortality obtained from Danish national registers from Marc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
0
6
0
1
Order By: Relevance
“…Although a few drinks every now and then most likely are harmful, a previous study has shown that CABG patients who consume >21 units of alcohol per week have a 2.4-fold risk of dying compared to moderate consumers. 30 More focus should, therefore, be given to assessing excessive alcohol use pre-and postoperatively in patients undergoing CABG. The present results also highlighted the importance of risk assessment in CABG patients, as individuals in the fourth quartile of a risk score consisting of the top predictors of postoperative mortality had a 12-fold increased risk of dying compared with those in the first quartile.…”
Section: Discussionmentioning
confidence: 99%
“…Although a few drinks every now and then most likely are harmful, a previous study has shown that CABG patients who consume >21 units of alcohol per week have a 2.4-fold risk of dying compared to moderate consumers. 30 More focus should, therefore, be given to assessing excessive alcohol use pre-and postoperatively in patients undergoing CABG. The present results also highlighted the importance of risk assessment in CABG patients, as individuals in the fourth quartile of a risk score consisting of the top predictors of postoperative mortality had a 12-fold increased risk of dying compared with those in the first quartile.…”
Section: Discussionmentioning
confidence: 99%
“…Отмечается роль чрезмерного потребления алкоголя. Так, среди потребляющих ≥22 единиц в неделю риск смерти от всех причин был в 2,2 раза выше по сравнению с остальными [30].…”
Section: предоперационные факторыunclassified
“…Moderate alcohol consumption is associated with a lower risk of CHD, and an association between moderate and low morbidity and mortality among patients with recent myocardial infarction has also been found (Maclure, 1993). A study of 1,919 patients undergoing aorto-coronary bypass assessed the association between alcohol consumption and mortality, showing that heavy drinkers showed an increased risk of mortality (Grabas et al, 2016).…”
Section: Alcohol Consumptionmentioning
confidence: 99%
“…Studies have shown that close to two-thirds of ACS patients exhibit mild to moderate OSA. Even mild levels of OSA with minimal daytime symptoms are associated with adverse effects on endothelial function and hypertension ( Kohler et al, 2008 ; Li et al, 2017 ). In the Nakashima (2015) study, close to half of all patients were diagnosed with moderate to severe OSA, a level that has been independently associated with 2.3 times the risk of recurrent ACS events after adjusting for covariates, such as age, sex, body mass index (BMI), smoking, and diabetes.…”
Section: Cardiac Patients Psychological and Psychosocial Variablesmentioning
confidence: 99%